Peran Mikroorganisme dalam Proses Degradasi Bahan Organik - Yuwan Marthyn Ziliwu; Natalia Kristiani Lase (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
The process of organic matter degradation is an integral part of the ecosystem cycle, which converts complex organic compounds into simpler forms through the activity of microorganisms. Microorganisms, such as bacteria, fungi, and actinomycetes, play an important role in the decomposition of organic matter, whether from household waste, crop residues, or organic industrial waste. This process involves various biochemical mechanisms, such as hydrolysis, fermentation, and oxidation, which are triggered by exocellular enzymes produced by microbes. Environmental factors, such as pH, temperature, humidity, and oxygen content, affect the efficiency of degradation by microorganisms. Several microorganisms, especially those that have the ability to decompose lignin, cellulose, and hemicellulose, have been widely applied in organic waste management technologies such as composting, bioremediation, and biogas production. Research on the role of microorganisms in organic matter degradation is not only important for understanding ecosystem dynamics, but also has the potential to support efforts to manage organic waste that are more environmentally friendly and sustainable. This abstract provides a review of the role, mechanisms, and factors that influence organic matter degradation by microorganisms, as well as their applications in environmental technology.